A new empirical relation between surface wave magnitude and rupture length for turkey earthquakes (2014)
Many practical problems encountered in quantitative oriented disciplines entail finding the best approximate solution to an over determined system of linear equations. In this study, it is investigated the usage of different regression methods as a theoretical, practical and correct estimation tool in order to obtain the best empirical relationship between surface wave magnitude and rupture length for Turkey earthquakes. For this purpose, a detailed comparison is made among four different regression norms: (1) Least Squares, (2) Least Sum of Absolute Deviations, (3) Total Least Squares or Orthogonal and, (4) Robust Regressions. In order to assess the quality of the fit in a linear regression and to select the best empirical relationship for data sets, the correlation coefficient as a quite simple and very practicable tool is used.A list of all earthquakes where the surface wave magnitude (Ms) and surface rupture length (L) are available is compiled. In order to estimate the empirical relationships between these parameters for Turkey earthquakes, log-linear fit is used and following equations are derived from different norms:for L2 Norm regression (R2=0.71),for L1 Norm regression (R2=0.92),for Robust regression (R2=0.75),for Orthogonal regression (R2=0.68),                           Consequently, the empirical equation given by the Least Sum of Absolute Deviations regression as  with a strong correlation coefficient (R2=0.92) can be thought as more suitable and more reliable for Turkey earthquakes. Also, local differences in rupture length for a given magnitude can be interpreted in terms of local variation in geologic and seismic efficiencies.  Furthermore, this result suggests that seismic efficiency in a region is dependent on rupture length or magnitude.  ResumenMuchos problemas prácticos encontrados en las disciplinas de orientación cuantitativa implican encontrar la mejor solución aproximada para un sistema determinado de ecuaciones lineales. En este estudio se investiga el uso de diferentes métodos de regresión tanto teóricos como prácticos y la herramienta de estimación correcta con el fin de obtener la mejor relación empírica entre la magnitud de onda superficial y la ruptura de longitud para los terremotos en Turquía. Para este propósito se hace una comparación detallada a partir de cuatro normas diferentes de regresión: (1) mínimos cuadrados, (2) mínimas desviaciones absolutas, (3) mínimos cuadrados totales y (4) regresiones robustas. Con el fin de evaluar la regresión lineal adecuada y seleccionar la mejor relación empírica de grupos de datos empíricos, la correlación de coeficiente es una herramienta simple y muy práctica. Se compiló una lista de todos los terremotos donde se cuenta con la magnitud de onda superficial (Ms) y la ruptura de longitud superficial (L). Con el fin de determinar las relaciones empíricas entre estos parámetros para los terremotos de Turquía, se utiliza la regresión lineal adecuada y las siguientes ecuaciones se derivan de diferentes reglas.Ms = 1.02* LogL + 5.18, para la regresión normal L2 (R2=0.71),Ms = 1.15* LogL + 4.98, para la regresión normal L1 (R2=0.92),Ms = 1.04* LogL + 5.15, para la regresión robusta (R2=0.75),Ms = 1.25* LogL + 4.86, para la regresión ortogonal (R2=0.68).Por consiguiente, la ecuación empírica dada por la regresión de desviaciones mínimas absolutas es con un fuerte coeficiente de correlación (R2=0.92) que sería más apropiado y más confiable para los terremotos de Turquía. También, las diferencias locales en la ruptura de longitud para una magnitud dada puede ser interpretada en términos de eficiencia sísmica y geológica en la variación local. Además, el resultado sugiere que la eficiencia sísmicaen una región depende de la ruptura de longitud o de la magnitud.